Hubungan antara academic self-concept dan academic self-efficacy dengan flow pada mahasiswa Universitas X - Lesmana, Teguh (Konsorsium Psikologi Ilmiah Nusantara, 2019)
Depression and loss of focus are symptoms experienced by some students, which could indicate the lack of flow. Academic self-concepts and academic self-efficacy are hypotesized to be related to students’ capacity to flow. The purpose of this study was to determine the relationship between academic self-concept and academic self-efficacy towards student’ capacity to flow. This quantitative study employed questionnaire for data collection, participated by 108 students at university X. The results showed a significant relationship between academic self-concept and academic self-efficacy towards students’ capacity to flow. Additional analysis demonstrated a significant relationship between academic self-concept and academic self-efficacy with student’s GPA, while flow was not related to student’s GPA.